The Impact of Government Policy to Raise Subsidized Fuel Oil Prices on City Transportation in the City of Medan - Ardian, Muhammad; Maha, Kevin Benammi Imanuel; Saragih, Jesly Alberto; Pakpahan, Leo Partogi (Journal of Sumatera Sociological Indicators, 2023)
This study aims to see the impact of the increase in subsidized fuel on public transportation in the city of Medan. This study uses a qualitative method with a case study approach. Primary Data Collection Techniques through interviews with City Transportation Drivers in Medan City. The secondary data is obtained from journals, reports, and online media. The results of the study show that the increase in fuel prices does not only have an impact on city transportation drivers in Medan City, but also on the passengers. In addition, the government needs to pay attention to the increase in the price of public transportation fares in the city of Medan. Because City Transportation has become the most popular transportation because the price is affordable. If there is an increase that is too high, it will be very burdensome for the community.